Knowledge and Practice of Nursing Ethics and its Influence on Student Nurses Behaviour in Nursing Schools in Benin City, Nigeria. - Aikabeli Priscilla O; Agbeyegbe Jemine (International Journal of Educational Excellence and Innovation, 2024)
Nursing ethics is an integral part of nursing knowledge and practice which helps to avoid ethical issues and legal complications. This study aimed to examine the knowledge and practice of nursing ethics and its influence on student nurses' behaviour in nursing schools in Benin City, Edo State. The study also sought to examine the perception of student nurses on nursing ethics, the level at which nursing ethics is being taught in school of nursing and the factors militating against its practice in schools of nursing. The population for this study comprised of 82 student nurses from St. Philomena Catholic Hospital and 250 from Edo State College of Nursing Sciences both in Benin City, Edo State with a total of 332.the sample size determined by random sampling was 181. However, only 170 questionnaires were filled and returned.  The study adopted a cross-sectional research design. The instrument for data collection was a structured questionnaire designed to assess the knowledge and practice of nursing ethics among student nurses. Descriptive statistics was be used to summarize the demographic characteristics of the participants and the overall knowledge and practice of nursing ethics. The findings of this study revealed that most student nurses recognize the importance of ethical knowledge in their practice, aligning with the fundamental principles of nursing. The study also revealed that students generally perceive that their programme provide sufficient content related to nursing ethics, indicating a positive aspect of their educational experience. However, the demands of their academic programme may sometimes impede their ability to prioritize ethical considerations. Based on the findings, the study recommended that there should be a forum for all nurses at least once a month on mortality review to identify and forestall possible legal and ethical issues. The study also recommended that the Department of Nursing Services and the management of all hospitals should collaborate to sponsor nurses to seminars, workshops and symposia.